Position statement on the role of nurses in therapeutic patient education in atopic dermatitis. (21st July 2021) - Thormann, K.; Aubert, H.; Barbarot, S.; Britsch‐Yilmaz, A.; Chernyshov, P.; Deleuran, M.; El‐Hachem, M.; de Groot, J.; Heratizadeh, A.; Raymakers, F.; Stalder, J.F.; Wollenberg, A.; et al.
Abstract: In chronic skin diseases such as atopic dermatitis (AD), therapeutic failure due to poor patient adherence to treatment is commonly reported. Therapeutic patient education (TPE) is an approach to improve self‐management and adherence. Several studies demonstrated that TPE programmes have positive effects on disease management resulting in decreased disease severity and improved quality of life in AD patients. Various healthcare professionals (dermatologists, nurses, psychologists, dieticians) have been involved. TPE performed by trained dermatology nurses are highly efficient and improve various health‐related outcomes. The aim of this position paper is to analyse the aims, modalities and efficacy of TPE in AD, to identify specific roles of dermatology nurses, to assess qualification requirements, and to propose practical recommendations. Potential activities of nurses in ongoing and future TPE programmes for AD patients will be discussed.